(untitled) (Research, Society and Development, 2021)
Enterococcus faecium is an important genus of probiotic acid lactic bacteria that forms an integral part of the healthy human microbiota. However, few studies relate the ability of food-borne Enterococcus faecium to prevent colorectal cancer, considered one of the main causes of mortality in Western countries, being among the three most incident cancers. Our study proposes to use a new approach to evaluate the potential of the Enterococcus faecium 137v - EF137v strain of artisanal “Coalho” cheese in its performance for prevention and delay in the progression of colorectal cancer in an animal model. To this end, we evaluated, through abdominal ultrasound, the effects of oral administration of EF137v on the development of colorectal cancer induced by 1,2-dimethylhydrazine - DMH in several groups aiming at a systemic analysis on the health of Wistar rats, as well as observations of possible changes in the weight and serum levels of these animals. The results obtained were important for the delay in tumor progression promoted by EF137v in rats that used the probiotic in isolation before (preventive) and after (dressing) the cancer induction. The rats had a stable body weight, with no sudden changes during the experiment. Serum triglyceride levels were high after cancer in most treated groups. A discussion on possible metabolic changes was initiated, as well as the protective function of EF137v against colorectal cancer. The probiotic EF137v proved to be a strong candidate as a preventive agent for the development of cancer and the ultrasound procedure is an additional tool to accompany important changes in the intestine.